Pengembangan Modul Pembelajaran Pengolah Lembar Kerja Excel Berbasis Multimedia [Developing an Excel Spreadsheet Multimedia Learning Module] - Yanuard Putro Dwikristanto; Tanti Listiani (Universitas Pelita Harapan, 2018)
Competence in the use of Information and Communication Technology (ICT) has become a part that is needed to be mastered by prospective student-teachers. Students are expected to use ICT appropriately in education. The problem that often happens is that many students have difficulty working on tasks outside the classroom, especially when Microsoft Excel. Many students appear to understand and look like they are able follow guided practice in class, but outside of class they are confused and often forget the instructions given by lecturers. One solution for dealing with these problems is to provide learners with a multimedia module for learning how to create and use spreadsheets. It is hoped that this module will help students to solve their learning difficulties in ICT courses including those with different learning styles. The purpose of this research is to evaluate the usefulness of this multimedia module. The development of this module was done by using the ASSURE model which consists of six stages: (1) analyze the learners; (2) state objectives; (3) select appropriate methods, media, and materials; (4) utilize materials; (5) require learners’ participation; and (6) evaluate and revise. The results of the questionnaire indicate that candidate teachers tend to be stronger in learning through Visual-Auditory ways. In addition, student mastery of the Excel Sheet processing program has the lowest value of Word and PowerPoint programs. The design of this learning module will be made by taking into account the Visual-Auditory aspects of the Microsoft Excel topic. This learning module will be developed with an interactive design using the PowerPoint 2016 program. BAHASA INDONESIA ABSTRAK: Kompetensi penggunaan Teknologi Informasi dan Komunikasi (TIK) menjadi bagian yang perlu dikuasai oleh mahasiswa calon guru. Mahasiswa diharapkan dapat menggunakan TIK secara tepat dalam dunia pendidikan. Permasalahan yang sering terjadi adalah banyak mahasiswa yang mengalami kesulitan saat pengerjaan tugas di luar kelas, khususnya penggunaan Microsoft Excel. Banyak mahasiswa yang mampu dan paham mengerjakan praktik terbimbing di kelas, namun ketika di luar kelas mereka mengalami kebingungan dan lupa akan instruksi yang diberikan oleh dosen. Untuk menjawab permasalahan tersebut maka diberikan solusi yaitu pemberian modul pembelajaran pengolah lembar kerja excel berbasis multimedia. Pengembangan modul pembelajaran pengolah lembar kerja excel berbasis multimedia diharapkan dapat memecahkan masalah kesulitan belajar mahasiswa pada mata kuliah TIK. Tujuan dari penelitian ini adalah untuk mengembangkan modul pembelajaran pengolah lembar kerja excel berbasis multimedia. Dengan diberikan modul pembelajaran ini diharapkan dapat mengakomodasi kebutuhan mahasiswa yang memiliki gaya belajar berbeda-beda. Pengembangan modul ini dilakukan dengan menggunakan model ASSURE yang terdiri dari enam tahap, yaitu: analyze learners; states objectives; select methods, media, and materials; utilize materials; require learners participation; dan evaluate and revise. Hasil angket menunjukkan bahwa gaya belajar mahasiswa guru lebih kuat kepada Visual-Auditori. Selain itu, penguasaan mahasiswa terhadap program pengolah Lembar Kerja Excel memiliki nilai yang paling rendah daripada program Word dan PowerPoint. Rancangan modul pembelajaran ini akan dibuat dengan memperhatikan aspek Visual-Auditori pada topik Microsoft Excel. Modul pembelajaran ini akan dikembangkan dengan desain interaktif menggunakan program PowerPoint 2016.